2005
DOI: 10.1093/toxsci/kfi344
|View full text |Cite
|
Sign up to set email alerts
|

The Aryl Hydrocarbon Receptor Directly Regulates Expression of the Potent Mitogen Epiregulin

Abstract: 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) is known to cause a large number of adverse effects, mediated largely by its binding to the aryl-hydrocarbon receptor (AhR) and subsequent modulation of gene expression. It is thought that AhR mediates these effects through the untimely and disproportionate expression of specific genes. However, the exact mechanism, or the genes involved, through which TCDD leads to these effects is still unknown. This study reports the discovery of a novel target gene, epiregulin, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 40 publications
2
42
2
1
Order By: Relevance
“…Although the mechanism through which the AhR regulates Slug is still under investigation, the possibility that AhR and c-Rel coregulate the Slug promoter is appealing, given past work showing cooperation between AhR and the p65 NF-nB subunit (34). Lastly, our findings are consistent with results of other investigators suggesting a role for exogenous ligand-activated AhR in regulating factors involved in branching and invasive growth such as Slug (18), epiregulin (35), and Cox II (36) in human mammary tumor lines and in other cell types.…”
Section: Discussionsupporting
confidence: 91%
“…Although the mechanism through which the AhR regulates Slug is still under investigation, the possibility that AhR and c-Rel coregulate the Slug promoter is appealing, given past work showing cooperation between AhR and the p65 NF-nB subunit (34). Lastly, our findings are consistent with results of other investigators suggesting a role for exogenous ligand-activated AhR in regulating factors involved in branching and invasive growth such as Slug (18), epiregulin (35), and Cox II (36) in human mammary tumor lines and in other cell types.…”
Section: Discussionsupporting
confidence: 91%
“…a-naphthoflavone, an AhR antagonist, diminished PMinduced secretion of amphiregulin and TGF-a ( fig. 3), suggesting AhR-dependent transcriptional regulation of amphiregulin and TGF-a, which has already been described for another EGFR ligand, epiregulin, in 2,3,7,8-tetrachlorodibenzo-pdioxin-treated mouse cells [25]. This hypothesis is reinforced by the identification of consensus xenobiotic responsive element sequences upstream of the transcriptional start site in human amphiregulin and TGF-a promoters, to which a transcriptional complex including PAH and AhR binds to transactivate genes.…”
Section: Pm25-induced Egfr Ligands Mediate a Pro-inflammatory Responmentioning
confidence: 55%
“…Historically, the AhR has been studied for its responsiveness to a variety of environmental chemicals (e.g., polycyclic aromatic hydrocarbons, PCBs, and dioxins) and its ability to transactivate genes encoding phase I cytochrome P-450 enzymes that metabolize endogenous substrates (e.g., 17b-estradiol) and some environmental chemicals into mutagenic intermediates [Safe and Krishnan, 1995;Spink et al, 2003]. However, more recent studies have indicated roles for the AhR, even in the absence of environmental ligands, in the transcriptional regulation of genes critical for growth [Ma and Whitlock, 1996;Elizondo et al, 2000;Tohkin et al, 2000;Abdelrahim et al, 2003;Patel et al, 2006], apoptosis Patel et al, 2006;Wu et al, 2007], and in EMT and tumor progression [Mulero-Navarro et al, 2005]. For example, immortalized mouse mammary fibroblasts lacking AhR have impaired tumorigenicity in a subcutaneous mouse xenograph model [Mulero-Navarro et al, 2005], and DMBA treatment induced a more highly invasive phenotype in c-Rel-driven mammary tumor cell line [Shin et al, 2006].…”
Section: Slugmentioning
confidence: 99%